2019
DOI: 10.1111/dth.13045
|View full text |Cite
|
Sign up to set email alerts
|

Pachyonychia congenita responding favorably to a combination of surgical and medical therapies

Abstract: Pachyonychia congenital (PC) is a rare genetic disorder of cornification and is classified into five types on the basis of keratin gene involved. There are no established treatment options available for PC. Sirolimus in both topical and oral form has been studied in management of PC. We report a young female with a novel genetic mutation in KRT6A gene who presented with painful palmoplantar hyperkeratosis and onychogryphosis, which was cosmetically disfiguring. She was prescribed oral sirolimus after all inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Daroach et al found that nail plate avulsion in combination with oral sirolimus significantly improved pain, but did not prevent the regrowth of abnormal nail plates and, consequently, was only of temporary benefit. 4,[6][7][8] Control of the hypertrophic nail plates by amputation of the distal phalanx, while effective, is unacceptably extreme. 9 Cosman et al reported nail plate, GME, and pSME followed by full-thickness skin graft coverage with the remaining nail bed developing hyperkeratinization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daroach et al found that nail plate avulsion in combination with oral sirolimus significantly improved pain, but did not prevent the regrowth of abnormal nail plates and, consequently, was only of temporary benefit. 4,[6][7][8] Control of the hypertrophic nail plates by amputation of the distal phalanx, while effective, is unacceptably extreme. 9 Cosman et al reported nail plate, GME, and pSME followed by full-thickness skin graft coverage with the remaining nail bed developing hyperkeratinization.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 Many treatments for PC focus on pain management with Botox injection and sirolimus, which has shown some efficacy in managing symptoms. 1 4 We present our experience and results of treating a pediatric patient with a combination of germinal matrix excision (GME) alone, GME with partial sterile matrix excision (pSME), and GME with complete sterile matrix excision (cSME).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been evaluated in XP fibroblast cell lines carrying a homozygous deletion in exon 9 of the XPC gene ( Dupuy et al, 2013 ). Although a correction in only 2.5% of the cells was attained, the investigators suggested this may be sufficient for clinical efficacy.…”
Section: Restoring the Underlying Gene Defect/productmentioning
confidence: 99%
“…Today, PC has been categorized into five types according to the underlying keratins genes mutations (KRT6A, KRT6B, KRT6C, KRT16 and KRT17) resulting in structural alterations in keratin proteins [83][84][85].…”
Section: Pachyonychia Congenitamentioning
confidence: 99%